The role of gender inequities in women's access to reproductive health services: a population-level study of Simiyu Region Tanzania - Jane Tesha; Agatha Fabian; Serafina Mkuwa; Gaspery Misungwi; Frida Ngalesoni (BMC, 2023)
Abstract Background Amref Health Africa, with support from Global Affairs Canada, examines if women's access to reproductive health services in Tanzania is affected by Gender social norms, decision-making power, roles and responsibility, and access to resources in relation to the utilization of reproductive Health Services in Tanzania. A Gender Need Assessment (GNA) was conducted in five districts in ' 'Tanzania Simiyu Region to improve the infrastructure, supply, quality, and demand for integrated Reproductive, Maternal, Newborn, and Child and Adolescent Health (RMNCAH), Nutrition, and Water, Sanitation, and Hygiene (WASH) services. The analysis identifies gender as a fundamental maternal and child health driver through existing gender inequality at the household and community levels that dictates women's status. Methods The qualitative assessment involved data collected from gender- and age-desegregated focus group discussions (FGDs) and in-depth interviews (IDIs) of key informants in three districts; Bariadi, Busega, and Meatu, in Simiyu region, Tanzania. Participants comprised 8-10 married women and men, unmarried women and men, and adolescent boys and girls. A total of 129 participants were involved in the FGDs. Results This paper reports the critical drivers influencing gender inequality in Simiyu by detailing how Gender inequality affected women's access to reproductive health care in relation to; gender social norms, decision-making power, access to resources at the household and community level, roles and responsibilities, including men's and 'boys' roles are more valued than the roles and responsibilities of women and girls resulted to limited free time to do things for themselves, such as visiting the health facilities for RMNCAH. Conclusions This paper explored gender-based enablers and/or barriers influencing women and girls' realization of their sexual and reproductive health and rights. It was found that social norms, decision-making powers, and lack of access to and control over resources presented as key barriers. In contrast, continuous community sensitization and increased scope of women's participation in decision-making served as enabling environment to overcome gender inequities that influence woman's use of RMNCAH services in Tanzania. Such insights will shape interventions geared towards valuing differences in a manner that overcome gender inequities that influence woman's use of RMNCAH services in Tanzania.